Narrativas de estagiários e memórias: a formação de professores a partir do dito/ escrito/ lembrado - Schmidt, Magda (2014)
This study was developed under the guidance of the Graduate Studies Program in Education at the Federal University of Santa Maria Brazil (UFSM-BR) and is inserted into the LP1 line of research: education, knowledge and professional development of teachers. This study aims to analyze the narratives of five student teachers from the Biology Program in order to reflect upon these narratives and autobiographical memories to see what is going on within their teacher education. In order to clarify a bit more on formative aspects and demonstrate what paths were trailed to outline this research, the research begins by reporting early recollections which are portraits of the professional I myself have become. It is based on a qualitative, case study, methodological approach and aimed to analyze, through the narratives derived from five student teachers enrolled in the course Supervised Curricular Student Teaching in Elementary Education in 2012 as well as the formative aspects that permeate the narrative and autobiographical memories. Afterwards, some references which deal with the theme of teacher education to elucidate what kind of educational research dealing with this topic is brought to light. The fifth part of this work begins by analyzing the narratives of future teachers through three categories that were created from relevant issues that arose from the speech of the student teachers. These categories, which were denominated: supervised student teaching, student teaching in Biology and being a teacher, were listed and related to the idea of teaching knowledge brought by Tardif (2002). Finally, I sum up by bringing into the discussion a few issues considered relevant to be thought over and discussed, such as teacher education at the university, the structure of the Biology undergraduate teacher education program at the Federal University of Santa Maria and what is actually meant by being a teacher and how frustrating it can be to rely upon an idealized professional.